Sequencing Grade Tandem Mass Spectrometry for Top–Down Proteomics Using Hybrid Electron Capture Dissociation Methods in a Benchtop Orbitrap Mass Spectrometer - Shaw, Jared B. (Anal Chem, 2018)
Compared to traditional collision induced dissociation methods, electron capture dissociation (ECD) provides more comprehensive characterization of large peptides and proteins as well as preserves labile post-translational modifications. However, ECD experiments are generally restricted to the high magnetic fields of FTICR-MS that enable the reaction of large polycations and electrons. Here, we demonstrate the use of an electromagnetostatic ECD cell to perform ECD and hybrid ECD methods utilizing 193 nm photons (ECuvPD) or collisional activation (EChcD) in a benchtop quadrupole–Orbitrap mass spectrometer. The electromagnetostatic ECD cell was designed to replace the transfer octapole between the quadrupole and C-trap. This implementation enabled facile installation of the ECD cell, and ions could be independently subjected to ECD, UVPD, HCD, or any combination. Initial benchmarking and characterization of fragmentation propensities for ECD, ECuvPD, and EChcD were performed using ubiquitin (8.6 kDa). ECD yielded extensive sequence coverage for low charge states of ubiquitin as well as for the larger protein carbonic anhydrase II (29 kDa), indicating pseudo-activated ion conditions. Additionally, relatively high numbers of d- and w-ions enable differentiation of isobaric isoleucine and leucine residues and suggest a distribution of electron energies yield hot-ECD type fragmentation. We report the most comprehensive characterization to date for model proteins up to 29 kDa and a monoclonal antibody at the subunit level. ECD, ECuvPD, and EChcD yielded 93, 95, and 91% sequence coverage, respectively, for carbonic anhydrase II (29 kDa), and targeted online analyses of monoclonal antibody subunits yielded 86% overall antibody sequence coverage.